2022
DOI: 10.3390/buildings12081074
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Model for the Impact of Building Control and Automation Upgrade on Space Heating Energy Efficiency

Abstract: Intelligent building management systems are proven to lead to energy savings and are an integral component of smart buildings. The procedures developed in the EN standards describe the methodology for calculating the energy savings achieved by improving the automation and control levels of separate services in building systems. However, although this method is used in practice, it is rarely applied or investigated by the research community. Typically, energy savings resulting from a single automation improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Additionally, the concept of "smartness in the built environment" is emerging in the retrofitting of buildings, seeking to attain greater sustainability, efficiency, automation, and adaptability through "real-time interaction" [8]. Within this context, specific research areas that pose contemporary challenges include environmental and structural performance assessment [9], real-time plug load identification [10], energy efficiency [11], indoor thermal comfort [12] and, in connection with this, the IAQ monitoring systems [13]. Moreover, the application of IoT-enabled optimal control for HVAC systems is being implemented [14], incorporating design considerations such as occupant behaviour, building typology, and cost functions in relation to modelling approaches and optimisation algorithms [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the concept of "smartness in the built environment" is emerging in the retrofitting of buildings, seeking to attain greater sustainability, efficiency, automation, and adaptability through "real-time interaction" [8]. Within this context, specific research areas that pose contemporary challenges include environmental and structural performance assessment [9], real-time plug load identification [10], energy efficiency [11], indoor thermal comfort [12] and, in connection with this, the IAQ monitoring systems [13]. Moreover, the application of IoT-enabled optimal control for HVAC systems is being implemented [14], incorporating design considerations such as occupant behaviour, building typology, and cost functions in relation to modelling approaches and optimisation algorithms [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, EN ISO 52120-1:2022 [28] and the previous, recently repealed, EN-15232-1 [29] have introduced a specific methodology for energy savings through the concept of TBM functions [30]. Many studies demonstrate this process improvement, such as [25], which calculates the discounted payback period; [31], which includes a BAC audit tool; [32], which calculates the lighting systems; and [11], which evaluates the savings of the heating systems. Nevertheless, some research has concluded that this method does not provide a reliable estimate of achievable energy savings because it does not take into account other factors, such as building and installation design parameters (e.g., type, dimensions, envelope, air exchanges, settings) and contextual factors (e.g., occupant behaviour, climate zone, latitude, and orientation) [33].…”
Section: Introductionmentioning
confidence: 99%